Scalable and enhanced key-aggregate cryptosystem in cloud-based intelligent health monitoring system - Arumugam, K.; P. Sumathi, Dr. (International Journal of Engineering and Technology, 2019)
Cloud based Intelligent Health Monitoring system (CIHMS) is a fashionable technology that enables the patients to retrieve health care details directly without visiting the hospital. This can be accomplished by storing the health care details of the patients in the cloud environment. But securing the healthcare details is a challenging problem. In this manuscript, Scalable and Enhanced Key-Aggregate Cryptosystem (SE-KAC) is proposed to provide efficient security for healthcare details. This method addresses the prob-lem of leakage of sensitive information and designs a Secure Cloud-based Intelligent Health Monitoring system for providing the security of the concerned parties and their data. This method allows the patient and healthcare institutions (HIs) to store the health and medical prescription data in encrypted format. For encrypting the data, the double encryption method with ciphertext-id called classes for improving the security. The key owner has a master secret key that is used to extract the secret keys for different classes. The extracted key is aggregated and sends as a single aggregate key to the patient for the decryption process. Elliptic curve is used to generate the ciphertext-id dynamically depends on the data size. An experimental result shows that proposed SE-KAC achieves high security and less complexity.Â Â